Borrowing place brands: product branding from SMEs in the publishing industry. Issue 2 (16th December 2019) - Noorda, Rachel L.
Abstract : Purpose: The purpose of this paper is to empirically test how company size affects the use of Scotland's place brand in product branding by small and medium-sized enterprises (SMEs) in the book industry in Scotland. Design/methodology/approach: This paper uses a mixed-method approach to investigate place brand adoption for product branding by SMEs in the Scottish book industry through the analysis of Scotland's place brand identifiers in a corpus of 208 online book blurbs. Findings: Results from the analysis show that, amongst SMEs in the Scottish publishing industry, smaller companies are more likely to use Scotland place brand identifiers in product marketing. Originality/value: This is the first study to analyze book blurbs from a marketing perspective and it is one of the few articles on product-place co-branding. Additionally, branding in SMEs is a relatively new and uncharted area of research to which this study contributes, and branding in book publishing is also a scarcely researched area, to which this study offers new, empirical data about the relationship between place brands and product brands.